Prevalence and Distribution of Oral Mucosal Lesions by Sex and Age Categories: A Retrospective Study of Patients Attending Lebanese School of Dentistry - Sami El Toum; Antoine Cassia; Nermine Bouchi; Issam Kassab (International Journal of Dentistry)
Background. Prevalence and distribution of oral mucosal lesions in a sample of Lebanese population attending the School of Dentistry of Lebanese University is necessary to evaluate their oral health situation. Objectives. The aim of the present study was to determine the prevalence and distribution of oral mucosal lesions of patients attending the School of Dentistry. Methods. A descriptive study was carried out by retrospectively examining a total of 231 medical and clinical examination record files of patients, attending the School of Dentistry Lebanese University for multidisciplinary dental treatments. 178 medical records were retained. Each medical and clinical examination record was done by an undergraduate student and then evaluated by a doctor. The record file included a civil status, chief complaint, medical history, and extraoral and intraoral clinical examination during the period between October 2014 and May 2015. Exclusion criteria were lack of written information in their medical and clinical examination record and being nonevaluated by a doctor. Data regarding age, gender, socioeconomic status, chief complaint, systemic diseases, and drugs intake were collected by using a questionnaire while the type of extraoral and oral mucosal lesions by clinical examination. Results. The sample consisted of 102 (57.3%) females and 76 (42.7%) males. The age ranged from 10 to 92 years with a mean age of 40.1 years. Among these subjects, 110 (61.8%) presented with one or more lesions. All patients were Lebanese. The most common lesion diagnosed was coated/hairy tongue affecting 17.4% of the subjects, followed by melanotic macule (11.2%), gingivitis (9.6), linea alba (6.2%), tongue depapillation (5.1), leukoplakia (5.1), traumatic fibroma (4.5), frictional keratosis (3.9%), fissured tongue (3.9%), hemangiomas (3.9%), Fordyce granules (3.9%), dry mucosa (3.4), angular cheilitis (2.2), gingival hyperplasia (2.2), and crenulated tongue (1.7%). Overall, the prevalence of oral mucosal lesions did not significantly differ between sex and age groups. Conclusions. The high prevalence of oral mucosal lesions necessitates adequate awareness and management of these lesions in the general population. Dental clinicians should be knowledgeable and familiar with the etiopathogenesis, clinical presentation, diagnosis, and management of these lesions.